Five control systems preventing transfer of Escherichia coli K-12 sex factor F. - Gasson, M J (1975)
The transfer inhibition systems of 28 Fin+ plasmids have been characterized, using Flac mutants insensitive to inhibition by R100 or R62. All F-like plasmids (except R455) and one N group plasmid determined systems analogous to that of R100; this is designated the FinOP system. None of these plasmids could supply a FinP component of the transfer inhibitor able to replace that of F itself. In addition to the FinOP and R62 transfer inhibition systems described previously, new systems were encoded by the F-like plasmid R455, the I-like plasmid JR66a, and the group X plasmid R485. Besides inhibiting F transfer, JR66a also inhibited F pilus formation and surface exclusion, whereas R485 inhibited only pilus formation and R455 inhibited neither. All three R factors inhibited transfer of J-independent Flac elements, indicating that they act directly on one or more genes (or products) of the transfer operon, rather than directly via traJ. The tral products and transfer origin sequences of two Fin+ F-like plasmids, ColB2 and R124, appear to have similar specificities to those of F itself.